Influence of studs shape and different pitch conditions on rugby athlete sprinting performance - Sharul Nizam, Turiman (2023)
In rugby, a player's sprinting prowess emerges as a pivotal determinant for bridging the gap to adversaries and eluding their pursuit. Hence, a proper rugby boot assumes paramount importance in enhancing sprinting capabilities. However, the tropical climate conditions in Malaysia, with high temperatures, humidity and heavy rainfall, possess the potential to rapidly degrade rugby pitch conditions, thereby exerting a pronounced impact on sprinting performance. This study investigated how different boot studs affected junior rugby players' sprinting performance on different pitch conditions, namely normal, puddle, and muddy surfaces. A cohort of 36 rugby players completed the sprinting tests with different boot stud shapes, i.e. cone, triangular, and blade shapes. For precise categorization of pitch attributes, a Speedy-Moisture test was carried out to quantify the proportion of soil water content. The sprinting trials are methodically orchestrated, incorporating fully automated timing gates sited strategically at the 0m and 40m demarcations along the track. The experiment data was examined statistically using Cohen's d effect size method, Pearson correlation, and ANOVA. The investigation revealed that the player's sprinting performance declined by 1.26% on the puddle pitch surface and by 16.51% on the muddy pitch surface compared to a regular normal pitch. In addition, rugby players in the normal BMI category also sprinting faster at a rate of 9.3% to 13.06% compared to overweight and obese players. Intriguingly, an intricate dissection of puddle pitch condition discloses that players with overweight BMI and in the forward position sprint faster when wearing boots with cone and blade studs. In contrast, on muddy pitch surfaces, the players in all positions and BMI groups wearing cone and triangle studs outperformed the blade studs. In essence, this study demonstrated the sprinting evaluation framework on various pitch conditions. Furthermore, it imparts invaluable technical insights to rugby players and coaches in selecting appropriate boots, particularly within Malaysia's distinctive climatic and pitch conditions.